TINJAUAN EFISIENSI SALURAN IRIGASI PADA JARINGAN UTAMA DAERAH IRIGASI KRUENG TUAN KABUPATEN ACEH UTARA - Teuku Johan Maulana; Ella Meilianda; Masimin Masimin (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2020)
Irrigation Network Krueng Tuan North Aceh Regency was built in 1994 with 11,150-meter primary channel that is planned can irrigate paddy fields potential 2,226 ha. The Krueng Tuan irrigation area has enormous potential as a food granary, but the irrigation discharge to irrigate rice fields was reduced due to a decline in the functioning of facilities in the Krueng Tuan irrigation network considering the age of buildings that were already age-consuming. This condition can result in an increase in water losses that affect the efficiency of irrigation in the channel. The method used to analyze the efficiency of irrigation channels using the inflow-outflow method. The data were recorded about cross-section dimensions of the channel and measuring flow velocity using the current meter. The results of the efficiency analysis show that there are four primary channel sections was under the theoretical efficiency values, namely the measurement section BT-02 - BT-03 at 88.729%, where water losses are caused by the influence of the physical conditions of the channel on the wall and the bottom and wild leads from the channel using the pump house. Other sections are BT-06 - BT-07 at 80.378%, BT-07 - BT-08 at 73.975%, and BT-08 - BT-09 at 67.094%. Water losses on all channels are caused by the physical condition of the channel that has been damaged in the channel wall and leakage due to the rat hole so that water seeped out of the channels.